Managing children with frequent respiratory infections and associated wheezing: a preliminary randomized study with a new multicomponent nasal spray - Tosca, Maria Angela; Varricchio, Attilio; Schiavetti, Irene; Naso, Matteo; Damiani, Valerio; Ciprandi, Giorgio (Allergologia et Immunopathologia, 2024)
Background: Preschoolers frequently have respiratory infections (RIs), which may cause wheezing in some subjects. Type 2 polarization may favor increased susceptibility to RIs and associated wheezing. Non-pharmacological remedies are garnering increasing interest as possible add-on therapies. The present preliminary study investigated the efficacy and safety of a new multi-component nasal spray in preschoolers with frequent RIs and associated wheezing.Methods: Some preschoolers with these characteristics randomly took this product, containing lactoferrin, dipotassium glycyrrhizinate, carboxymethyl-beta-glucan, and vitamins C and D3 (Saflovir), two sprays per nostril twice daily for 3 months. Other children were randomly treated only with standard therapy. Outcomes included the number of RIs and wheezing episodes, use of medications, and severity of clinical manifestations.Results: Preschoolers treated add-on with this multicomponent product experienced fewer RIs and used fewer beta-2 agonists than untreated children (P = 0.01 and 0.029, respectively).Conclusions: This preliminary study demonstrated that a multicomponent product, administered add-on as a nasal spray, could reduce the incidence of RIs and use of symptomatic drugs for relieving wheezing in children.